PENGARUH PROFITABILITAS, STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN: STUDI PADA PERUSAHAAN SEKTOR FINANCIALS SUBSEKTOR BANKS YANG TERDAFTAR DI BEI - Adinda Sekar Ayu Nur Aini; Agus Endro Suwarno (LP2M Universitas Bina Bangsa, 2024)
Company value is a condition achieved by a company to attract the trust of an investor both from the company's performance and future prospects. This study aims to analyze the influence of profitability, capital structure, company size, and financial performance on the value of study companies in the financial sector of banks listed on the Indo Esia Stock Exchange in 2020-2022. The sampling technique used in this study is purposive sampling. A total of 96 companies have met the criteria as observation units. The analysis method used is multiple linear regression analysis. The results of the study provide empirical evidence that profitability, capital structure, and company size have no effect on company value. Meanwhile, financial performance affects the company's value